Mister Exam
Lang:
EN
EN
ES
RU
Other calculators
Integral Step by Step
Derivative Step by Step
Equation systems Step by Step
Identical expressions
(- two *x - five)/(x^ two + five *x + six)^ two = zero
( minus 2 multiply by x minus 5) divide by (x squared plus 5 multiply by x plus 6) squared equally 0
( minus two multiply by x minus five) divide by (x to the power of two plus five multiply by x plus six) to the power of two equally zero
(-2*x - 5)/(x2 + 5*x + 6)2 = 0
-2*x - 5/x2 + 5*x + 62 = 0
(-2*x - 5)/(x² + 5*x + 6)² = 0
(-2*x - 5)/(x to the power of 2 + 5*x + 6) to the power of 2 = 0
(-2x - 5)/(x^2 + 5x + 6)^2 = 0
(-2x - 5)/(x2 + 5x + 6)2 = 0
-2x - 5/x2 + 5x + 62 = 0
-2x - 5/x^2 + 5x + 6^2 = 0
(-2*x - 5) divide by (x^2 + 5*x + 6)^2 = 0
Similar expressions
(-2*x + 5)/(x^2 + 5*x + 6)^2 = 0
(-2*x - 5)/(x^2 + 5*x - 6)^2 = 0
(2*x - 5)/(x^2 + 5*x + 6)^2 = 0
(-2*x - 5)/(x^2 - 5*x + 6)^2 = 0
(-2*x - 5)/(x^2 + 5*x + 6)^2 = 0 equation
+ equation
Solve the equation!
The unknown in the equation:
v
Numerical solution:
Do search numerical solution at [
,
]